The acute effects of whole-body vibration on motor unit recruitment and discharge properties - Lecce, E.; Nuccio, S.; Del Vecchio, A.; Conti, A.; Nicolò, A.; Sacchetti, M.; Felici, F.; Bazzucchi, I. (Frontiers in Physiology, 2023)
Introduction: several studies have reported improved performance in response to whole-body vibration (WBV). This is likely achieved by modulation of the central nervous system (CNS). Reduced recruitment threshold (RT), which is the % of Maximal Voluntary Force (%MVF) at which a given Motor Unit (MU) is recruited, may be responsible for the force/power improvements observed. Methods: 14 men (25±2.3 years; BMI= 23.3±1.5 kg∙m2 MVF: 319.82±45.74 N) performed trapezoidal isometric contractions of the tibialis anterior (TA) at 35-50-70 %MVF before and after three conditions: WBV, STAND (standing posture), and CNT (no intervention). The vibration was applied through a platform for targeting the TA. High-density surface electromyography (HDsEMG) recordings and analysis were used to detect changes in the RT and Discharge Rate (DR) of the MUs. Results: Mean motor unit recruitment threshold (MURT) reached 32.04±3.28 %MVF before and 31.2±3.72 %MVF after WBV, with no significant differences between conditions (p> 0.05). Additionally, no significant changes were found in the mean motor unit discharge rate (before WBV: 21.11±2.94 pps; after WBV: 21.19±2.17 pps). Discussion: The present study showed no significant changes in motor unit properties that could explain the improvements in performance parameters documented in previous studies. Further investigations are needed to understand motor unit responses to different vibration protocols and the chronic effect of vibration exposure on motor control strategies.